1988
DOI: 10.1111/j.1476-5381.1988.tb11725.x
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism by which monoamine oxidase inhibitors give rise to a non‐calcium‐dependent component in the depolarization‐induced release of 5‐HT from rat brain synaptosomes

Abstract: 4 The elevation of the non-Ca2+-dependent component of release caused by the monoamine oxidase inhibitors was totally abolished by the inhibitors of the plasma membrane 5-HT carrier, chlomipramine (500 nM), citalopram (50 nm) and fluoxetine (1 JM). 5 The results suggest that the non-Ca2+-dependent component of release seen with high depolarizing concentrations of K+, particularly in the presence of monoamine oxidase inhibitors, is caused by the efflux of [3H]-5-HT through the plasma membrane carrier which see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…This functional restoration in vivo fits well with the potassium-and MDMA-induced releases of [ 3 H]5-HT observed in vitro in VMAT2 sertÀcre synaptosomes. The mechanism involved in the [ 3 H]5-HT release in VMAT2 sertÀcre synaptosomes is presently unclear, but three non-mutually exclusive possibilities can be discussed: (1) Release of [ 3 H]5-HT through the carrier (Evans and Collard, 1988). Although this was suggested to occur in VMAT2 KO mice (Fon et al, 1997), we do not presently have any data in Figure 6 The VMAT2 sertÀcre mutation decreased anxiety and locomotion but increased reactivity to stress.…”
Section: Discussionmentioning
confidence: 99%
“…This functional restoration in vivo fits well with the potassium-and MDMA-induced releases of [ 3 H]5-HT observed in vitro in VMAT2 sertÀcre synaptosomes. The mechanism involved in the [ 3 H]5-HT release in VMAT2 sertÀcre synaptosomes is presently unclear, but three non-mutually exclusive possibilities can be discussed: (1) Release of [ 3 H]5-HT through the carrier (Evans and Collard, 1988). Although this was suggested to occur in VMAT2 KO mice (Fon et al, 1997), we do not presently have any data in Figure 6 The VMAT2 sertÀcre mutation decreased anxiety and locomotion but increased reactivity to stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, at present there is little evidence in support of such a view compared with that supporting the carrier-mediated theory of Nicholls (25) reviewed above. Furthermore, it has been shown that other transmitters which normally show little non-Ca2+-dependent release, can be induced, under certain experimental conditions, to release transmitters through the relevent plasma membrane carrier by a nonCa2+-dependent process (28). Whatever mechanisms may be involved, the response to short-term hypoxia in cortical synaptosomes seems to be very similar to that seen following longer exposure to hypoxic conditions (9).…”
Section: The Effect Of Hypoxia On the Release Of [3h]glutamate From Hmentioning
confidence: 91%
“…In those experiments in which the effect of removing extracellular Ca a § was examined, Ca a+ was replaced isosmotically with Na +. This procedure had been shown in previous studies to completely abolish the release of 5-[3Hlhydroxytryptamine in response to a similar depolarizing pulse of K § (28). In tissue beds which received a hypoxic insult, the tissue was perfused with standard Krebs solution, or Ca2+-free Krebs solution for 7 minutes.…”
Section: Preparation Of Synaptosomes Incubation With [3h]glutamate Amentioning
confidence: 99%
“…Veratramine may act like p-chloroamphetamine or fenfluramine releasing 5-HT through a carrier-dependent mechanism (18). Recently, it has been shown that MAO inhibitors are able to increase a component of noncalcium dependent, depolarization-induced release of 3H-5-HT through the plasma membrance carrier (19). Therefore, a part of the non-calcium dependent release of 3H-5-HT evoked by veratramine may be due to the concurrent use of pargyline which was applied throughout the present release study.…”
Section: Discussionmentioning
confidence: 99%